Peningkatan Literasi dalam Pengelolaan Obat melalui Sosialisasi “Dagusibu” di Nagari Painan - Rasyadi, Yahdian; Marsellinda, Elsa; Ningsih, Wida; Wahyuni, Fitri; Mahdawanci, Yesi; Merwanta, Selvi (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
Because of insufficient education, the rising trend of people self-medicating poses a threat to proper drug handling, storage, and disposal. According to RISKESDAS (2013), there is a lot of medication storage, antibiotic overuse (without a prescription), and medication mistakes. The Painan Nagari Health Post in IV Jurai District, Pesisir Selatan Regency, which does not yet have chemists, implemented DAGUSIBU (Get, Use, Store, Throw Away) education initiatives to address this issue. Midwives and other health workers were socialised at the Health Post in July 2024 as part of the activity, which also included the erection of educational posters. The activity's outcomes demonstrated that participants' understanding of rational drug management, particularly the need of avoiding medication mistakes and improper disposal, had improved. By preparing students to serve their communities in response to actual needs, DAGUSIBU programs help fulfil the tridharma of higher education and make health care providers more effective change agents in the field of public health. In Painan Nagari, this endeavour may pave the way for long-term progress in public health.